Drifters and Delinquents: Commitment and Neutralization in Low- and High-Rate Offending Early Adolescents - Walters, Glenn D. (Crime & delinquency, 2023)
The purpose of this study was to compare drift/neutralization and criminal lifestyle interpretations of the neutralization-delinquency nexus in 1,005 (498 boys, 506 girls) youth (mean age?=?11.22?years) organized into three groups: no delinquency, low-rate delinquency, and high-rate delinquency. Findings showed that low-rate delinquent youth were as committed to conventional social relationships as nondelinquent youth and more committed to conventional relationships than high-rate delinquent youth. It was further noted that low-rate or drifting delinquents used neutralization techniques more often than nondelinquents but less often than high-rate delinquents. These results suggest that neutralization may be less a matter of relieving guilt after having violated the law than it is a way of constructing a moral value system that supports crime.